A Meta-Analysis of Psychology Students' Attitudes Towards Statistics to Address Statistics Anxiety In The Social Sciences - Wagenaar, Emma Kate (Rhodes University, Faculty of Humanities, Department of Psychology, 2020)
Statistics anxiety is a well-documented phenomenon amongst students which is a result of negative attitudes towards Statistics. This is especially prevalent in the Social Sciences with Psychology students, where research indicates a relationship between attitudes and achievement in Statistics courses. This research project aimed to investigate this relationship. My study took the form of a meta-analysis comparing Psychology students' attitudes towards statistics using the SATS, to their achievement in statistics/quantitative research methods courses. Results indicated a statistically significant relationship between the attitudes of Psychology students (r = 0.226, p is less than 0.05), quantified by their reported Affect, self-perceived Cognitive Competence, measure of Value and degree of Difficulty of Statistics, and their subsequent achievement in Statistics. The strongest correlations were noted for Affect (r = 0.247, p is less than 0.005) and Cognitive Competence (r = 0.29, p is less than 0.005) SATS scores. Heterogeneity was noted in Affect (IÂ² = 30.998%) and Difficulty (IÂ² = 54.248%). The study possessed limitations in the integration of other factors into the meta-analysis, availability of studies, and understanding of meta-analysis. Future Statistics attitudes research should include achievement measurements for more investigation into this relationship. This research will hopefully lead to more support in both quantitative research design and statistical training for postgraduate Psychology students at Rhodes University.
Keywords: Psychology -- South Africa; College students -- Attitudes; Statistics -- Study and teaching; Anxiety; Performance anxiety; Systematic review